In‐field genetic stock identification of overwintering coho salmon in the Gulf of Alaska: Evaluation of Nanopore sequencing for remote real‐time deployment. (24th February 2022) - Deeg, Christoph M.; Sutherland, Ben J. G.; Ming, Tobi J.; Wallace, Colin; Jonsen, Kim; Flynn, Kelsey L.; Rondeau, Eric B.; Beacham, Terry D.; Miller, Kristina M.
Abstract: Genetic stock identification (GSI) from genotyping‐by‐sequencing of single nucleotide polymorphism (SNP) loci has become the gold standard for stock of origin identification in Pacific salmon. The sequencing platforms currently applied require large batch sizes and multiday processing in specialized facilities to perform genotyping by the thousands. However, recent advances in third‐generation single‐molecule sequencing platforms, such as the Oxford Nanopore minION, provide base calling on portable, pocket‐sized sequencers and promise real‐time, in‐field stock identification of variable batch sizes. Here we evaluate utility and comparability to established GSI platforms of at‐sea stock identification of coho salmon ( Oncorhynchus kisutch ) using targeted SNP amplicon sequencing on the minION platform during a high‐sea winter expedition to the Gulf of Alaska. As long read sequencers are not optimized for short amplicons, we concatenate amplicons to increase coverage and throughput. Nanopore sequencing at‐sea yielded data sufficient for stock assignment for 50 out of 80 individuals. Nanopore‐based SNP calls agreed with Ion Torrent‐based genotypes in 83.25%, but assignment of individuals to stock of origin only agreed in 61.5% of individuals, highlighting inherent challenges of Nanopore sequencing, such as resolution of homopolymer tracts and indels. However, poor representation of assayed salmon in the queried baseline data set contributed to poor assignment confidence on both platforms. Future improvements will focus on lowering turnaround time and cost, increasing accuracy and throughput, as well as augmentation of the existing baselines. If successfully implemented, Nanopore sequencing will provide an alternative method to the large‐scale laboratory approach by providing mobile small batch genotyping to diverse stakeholders.